Perubahan Kandungan Nitrogen, Phospat dan Kalium pada Penyimpanan Pupuk NPK - Yuni Adiningsih (Balai Riset dan Standardisasi Industri Samarinda, 2016)
NPK fertilizer is fertilizer containing Nitrogen, Phosphate and Potassium elemen. There elements have easyly soluble in water ions and do not resist to the sun rays (heat) easyly volatility. Due to the treatment of indoor and outdoor storing, all of Nitrogen, Phosphate and Potassium elements decrease in concentration and the most significant effect of storing is the indoor storing.In the treatment of storing duration, the results of 2 weeks duration is diffferent with 4 weeks duration both for indoor and outdoor sloring. A long time storing decrease the concemretion of Nitrogen, Phosphate and Potassium in fertilizer. The result of moisture content testing of fertilizer treated with heat and rain are higher than the fertilizer stored indoor treatment.